The Bone-Protecting Efficiency of Chinese Medicines Compared With Western Medicines in Rheumatoid Arthritis: A Systematic Review and Meta-Analysis of Comparative Studies - Cai, Xiao; Chen, Xiu-Min; Xia, Xuan; Bao, Kun; Wang, Rong-Rong; Peng, Jian-Hong; Liu, Hai-Jun; Yang, Qiao-Wen; Yan, Jing-Yao; Wang, Mao-Jie; Yu, Hua; Lu, Jin-Jian; et al. (Frontiers in Pharmacology, 2018)
Abstract： Background: Rheumatoid Arthritis (RA) is a systemic autoimmune disease leading to joint destruction. The prevention of bone and cartilage destruction has raised more and more attention in recent years. Objective: To evaluate current evidences regarding the bone-protecting efficacy of Chinese medicine or the combination of Chinese medicine and Western medicine for RA. Methods: We comprehensively searched PubMed, Embase, the Cochrane Library (www.the cochranelibrary.com), the China National Knowledge Infrastructure (CNKI), the Database for Chinese Technical Periodicals (VIP), and SinoMed. We next performed a systematic review and cumulative meta-analysis of all randomized controlled trials (RCTs) assessing the two therapy methods. Results: 16 studies including 1171 patients were included in the final analysis. The results showed that Chinese medicine could significantly improve the bone mineral density (BMD) (mean difference [MD] = 0.05 /g•cm-2, 95 % CI [0.03, 0.08], P＜0.00001), decrease the serum matrix metalloproteinase 3 (MMP-3) ([SMD] = -2.84, 95% CI [-4.22, -1.47], P＜0.0001). Conclusions: Chinese medicine may provide an efficiently alternative choice for treatment of RA in terms of the bone-protecting efficiency. Given the inherent limitations of the included studies, future well-designed RCTs are required to confirm and update the findings of this analysis.